2005
DOI: 10.1093/fampra/cmi074
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prescribing between GPs. Impact of the cooperation with pharmacists and impact of visits from pharmaceutical industry representatives

Abstract: There was a negative correlation between quality of prescribing by solo GPs and frequency of visits by pharmaceutical industry representatives. In day-to-day practice, no measurable effects of the cooperation between solo GP and pharmacist on the quality of prescribing were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
(27 reference statements)
2
43
0
Order By: Relevance
“…These early findings may reflect physicians' traditionally held views of the pharmacists' role and scope of practice. Studies of family physician attitudes toward community pharmacists have shown that family physicians are typically conservative in their view of the pharmacist's role (Holden & Wolfson, 1996;Muijrers et al, 2005). These same studies describe the importance of precisely defining pharmacist responsibilities and that good relationships correlate with a more positive attitude toward pharmacist involvement in providing care to patients.…”
Section: Discussionmentioning
confidence: 97%
“…These early findings may reflect physicians' traditionally held views of the pharmacists' role and scope of practice. Studies of family physician attitudes toward community pharmacists have shown that family physicians are typically conservative in their view of the pharmacist's role (Holden & Wolfson, 1996;Muijrers et al, 2005). These same studies describe the importance of precisely defining pharmacist responsibilities and that good relationships correlate with a more positive attitude toward pharmacist involvement in providing care to patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although a few GPs indicated they participate in multidisciplinary team meetings, there seems to be room for improvement as regards embedding these meetings structurally. Because structured meetings with GPs and pharmacists around pharmacotherapy already exist (as in pharmacotherapy audit meetings), 34,35 these seem suitable to embed discussions around patients with complex polypharmacy. Medication reviews with patients can also facilitate medication management, but currently seem not to be structurally performed.…”
Section: Box 1 Findings Per Case Vignette Accompanied By Statementsmentioning
confidence: 99%
“…A number of studies have shown that recommendations and interventions from pharmacists, under controlled circumstances, can lead to an optimisation of drug use and a better prescription policy [23,[30][31][32][33][34]. We also found indications for the existence of this gap in previous research we carried out among general practitioners: also in this study, the quality of prescribing by the general practitioner was not correlated with the general practitioner's attitude towards the pharmacist's role, the way in which general practitioners cooperated with pharmacists, or the quality of the PTAM [35]. The cause of this gap possibly lies in the rather non-committal nature that characterises the present cooperation between general practitioners and pharmacists, both in day-to-day practice and in the PTAM [33,36].…”
Section: Discussionmentioning
confidence: 51%